2007
DOI: 10.1159/000104402
|View full text |Cite
|
Sign up to set email alerts
|

Sterilized Mosquito Net versus Commercial Mesh for Hernia Repair

Abstract: Background: In industrialized countries alloplastic meshes are routinely used for hernia repair. However, in developing countries they are rarely available or affordable. This study compares textile properties and tissue response of commercial polypropylene mesh (PM) vs. sterilized nylon mosquito net (MN). Methods: Textile properties were examined in vitro. In 12 goats one MN and one PM (5.5 × 8 cm) were implanted onto the posterior layer of the rectus sheath. Wound healing was clinically assessed. Histology w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 32 publications
0
25
0
1
Order By: Relevance
“…[19][20][21][22][23] Previous studies on the use of mosquito mesh in groin hernia repair have shown promising results with respect to tissue reaction, outcome, and cost-effectiveness. 19,[21][22][23][24][25][26] However, data from randomized trials are lacking to inform the safety and long-term effectiveness of this practice. The aim of the current randomized trial was to assess the outcomes of groin hernia repair performed with the use of a low-cost lightweight mesh as compared with a commercial lightweight mesh in a low-income country in sub-Saharan Africa.…”
mentioning
confidence: 99%
“…[19][20][21][22][23] Previous studies on the use of mosquito mesh in groin hernia repair have shown promising results with respect to tissue reaction, outcome, and cost-effectiveness. 19,[21][22][23][24][25][26] However, data from randomized trials are lacking to inform the safety and long-term effectiveness of this practice. The aim of the current randomized trial was to assess the outcomes of groin hernia repair performed with the use of a low-cost lightweight mesh as compared with a commercial lightweight mesh in a low-income country in sub-Saharan Africa.…”
mentioning
confidence: 99%
“…Hence long-term complications like chronic pain, foreign body reaction and bridging should be seen less frequently with polyethylene meshes [13]. In a comparative study of mosquito mesh with polypropylene mesh in goats, in spite of normal wound healing, a higher inflammatory response was seen in the mosquito mesh group [14]. However, since the polyethylene mesh is extremely inexpensive, commercial exploitation of this mesh will be economically unviable for multinational companies.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials of low‐cost nets on patients with inguinal, ventral, and incisional hernia showed good surgical outcomes, with no substantial difference from surgical meshes in the short‐term reliability …”
Section: Introductionmentioning
confidence: 99%
“…In relation to biochemical properties and prostheses interaction with host tissues, some studies are found concerning in vitro analysis or in vivo experiments in animal models. Wilhelm et al . carried out an experimental study in goats comparing a PP surgical mesh and non‐medical grade polyamide (PA) nets.…”
Section: Introductionmentioning
confidence: 99%